Potential Combination of Xanthone Compounds from Mangosteen Fruit (Garcinia mangostana) with Eugenol Compounds in Basic Leaf (Ocimum sanctum) as Alternative Therapy in Preeclampsia - Muhammad Al Farisi Sutrisno (Eureka Herba Indonesia, 2021)
Preeclampsia is a hyperdynamic condition that is syndromed by hypertension and proteinuria after 20 weeks of pregnancy. Preeclampsia incident is the first cause of 6- 8 % number morbidity/mortality maternity and fetus in the world. Preeclampsia is related to the disability of physiology adaptation that can decrease perfusion of uteroplacental. Xanthone derivatives in mangosteen have been reported to possess a wide range of biological properties, including antioxidant and antihypertensive activities. Eugenol is a primary component of basil oil. It is known for its antioxidant, antiinflammatory, and vasorelaxant actions. These beneficial effects of eugenol make it an excellent therapeutic candidate for the treatment of hypertensive disorders of pregnancy. This study wants to analyze the best available research evidence on the potential combination of xanthone compounds from mangosteen fruit (Garcinia mangostana) with eugenol compounds in basil leaf (Ocimum sanctum) as an alternative therapy in preeclampsia. A literature review was conducted in the electronic databases PubMed and Google Scholar using the index terms "xanthone" and "eugenol" and "hypertension" and "preeclampsia." All types of studies were included for this study, such as randomized controlled trials, systematic reviews, literature reviews, and pilot studies published between 2010 and 2021. Articles which not written in English were excluded from the study. This search resulted in 10 papers. Antioxidant properties of mangosteen peel extract compounds derived from xanthone, the most significant component is α-mangosteen and γ-mangosteen. Eugenol is vasorelaxant action by increasing the expression of its target genes, Sarco/endoplasmic reticulum Ca²⁺-ATPase and adequate potassium-calcium- activated potassium channels channel, thereby relaxing vascular smooth muscle cells and decreasing blood pressure. With this review, we suggest that eugenol, which is a vasorelaxant combined with xanthone which is an antioxidant by obstructing free radical and oxidative stress, can be a potent therapeutic for preeclampsia and intend to motivate researchers (e.g., chemistry, biology, pharmaceutical, and therapeutic areas) to provide evidence of these compounds for the management of preeclampsia.